ENSEÑANZA EN MEDICINA DE LA METODOLOGIA DEL DIAGNOSTICO CLINICO EN PEQUEÑOS GRUPOS CON INTERACCION PAUTADA - Olavegogeascoechea, Pablo A.; Buzzeta, Graciela I; Valsecchi, Sara G.; Antelo, José L.; Mango, Esteban; Montero, Guadalupe; Calvet, Mónica (European Scientific Journal, ESJ, 2014)
The best scenario for the diagnostic teaching method was working in small teaching groups, a practice that is widely accepted not only by teachers but also for students. As it is considered an ideal environment, it has some aspects that should be taken into account for getting the objectives. Thus, this work was carried out to promote a mode in group dynamics in two different groups and compare them in terms of qualitative and quantitative analysis. Sixty two students were included in control group and seventy four in the experimental group. They were doing in the 4th year at a Medical School program between 2010 and 2012.Both groups were compared not only in relation to student self-assessment and satisfaction but also continuous individual assessment, group assessment and written personal assessment. The comparison between groups was statistically significant at the beginning of works, while no significant differences were seen at the end. Regarding participation, difference between groups (p < 0.001) was observed in favor to experimental group. The systematization of interactions in small groups is possibly the most appropriate modality to incorporate skills due to increased student compromise and motivation.